Effectiveness of the Application of Cooperative Learning Models Type Group Investigation on Discrete Mathematics Courses at Informatics Engineering Study Program of Polytechnic of South Aceh - Asmaidi Asmaidi; Oktalia Triananda Lovita; Khairuman Azmi (LPPM Politeknik Aceh Selatan, 2019)
The results of student learning in the Informatics Engineering Program in the Discrete Mathematics course showed unsatisfactory results. there were 40 students who took part in the lecture. Students who get D and E scores are 18 people. the value of students who do not pass reaches 45%. In addition, student activities during the course of learning are very passive. Students only receive material delivered by lecturers and are not actively involved in learning. The problem formulation in this study is how the learning outcomes and learning activities of students are taught using the cooperative learning model type Group Investigation and conventional learning models in Discrete Mathematics courses in the Informatics Engineering Study Program in South Aceh Polytechnic?. The purpose of this study was to find out the learning outcomes and student activities while learning using the Group Investigation model. This type of research is a pure experiment with random design, pre-test, post-test. Research procedures go through several stages, namely initial observation, preparation, implementation, evaluation, and final results. The research subjects were Informatics Engineering students of South Aceh Polytechnic Semester II consist of two group, namely classes 2A and 2B. The data in this study is the test value on sequence and number series materials; and the observation of student activities during the learning process. Data collection techniques used in this study were test questions and student activity observation sheets. The analysis technique used were t-test statistical data and percentage formula. The results of the final test data analysis in both the experimental class (2A) and the control class (2B) using the t-test of two parties at a significant level α = 0.05 were obtained and . So the relationship obtained or . It can be concluded that student learning outcomes with cooperative learning model Group Investigation type are better than learning without using cooperative learning model Group Investigation type (conventional model) in Discrete Mathematics courses especially in Sequence and Series sub material in Informatics Engineering Study Program South Aceh Polytechnic. The average percentage of student activity during the three meetings was 75.40% and was in the very active category.